Tatak Pilipino [episode no. 77]. - FI. ([Quezon City ABS-CBN, 1992)
A unique display of Pilipino ways and style.
Bayang Magiliw (3 min.) -- Philippine flag (7 min.) -- Joey Ayala and Bagong Lumad (10 min.) -- Ambeth Ocampo's most intriguing Historical findings (10 min.) -- Ricarte Puruganan's art (15 min.)
In English and Pilipino.
Hosts, Jim Paredes and Gel Santos Relos.
Keywords: Ayala, Joey; Pruganan, Ricarte; Flags -- Philippines; National songs -- Philippines; Philippines -- History